Pencegahan Perilaku Seksual Remaja Berbasis Model Path Analysis: Peran Self-control, Penggunaan Media Sosial dan Budaya Sekolah - Indri Primadianty; Ince Annisah Adawiyah Arifin (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Sexual behavior has become a prominent issue among adolescents today, particularly concerning HIV-AIDS and the decreasing age at which teenagers begin dating, which places them at risk of engaging in unsafe sexual practices. Preliminary interviews revealed that adolescent sexual behavior is influenced by the high intensity of social media use, which provides wide access to both positive and negative content. This study aims to examine how social media use and school culture affect the prevention of adolescent sexual behavior, with self-control as a mediating variable. A cross-sectional survey design with a causal approach and path analysis model was employed. The study sample consisted of 394 high school students in Makassar. Data collection was conducted using questionnaires for all variables. The results indicate that the prevention of adolescent sexual behavior is significantly influenced by self-control, social media use, and school culture, both directly and indirectly, based on the tested path analysis model. Importantly, the findings highlight that self-control serves as a strong mediating variable between social media use and school culture in relation to the prevention of adolescent sexual behavior.